The socialist imperative : from Gotha to now - Lebowitz, Michael A. (Monthly Review Press, 2015)
In a little more than a decade, economist Michael A. Lebowitz has written several major works about the transition from socialism to capitalism: Beyond Capital(winner of the Deutscher Prize), Build It Now, The Socialist Alternative, and The Contradictions of "Real Socialism." Here, he develops and deepens the analysis contained in those pathbreaking works by tracing major issues in socialist thought from the nineteenth century through the twenty-first. Lebowitz explores the obvious but almost universally ignored fact that as human beings work together to produce society's goods and services,